Impact of integration time steps of rain drop size distribution on their double-moment normalization: a case study in northern Benin - Moumouni, Sounmaïla; Akponi, Fulgence Payot; Zahiri, Eric-Pascal; Lawin, Agnidé Emmanuel; Gosset, Marielle (Comptes Rendus. Géoscience)
This study analyzed the sensitivity of the double-moment normalization of rain drop size distributions (DSDs) to their integration time steps. Six DSD datasets measured at different integration time steps were modeled by the double-moment normalization method. Six couples of reference moments are used for the normalization. Three DSD models (gamma, generalized gamma and lognormal) are used for modeling. Statistical criteria are used to assess the estimation of the moments of the DSDs made by the models. As results, the analysis highlighted the dependence of the shape function parameters on the DSD integration time step. It is also noted that the three DSD models are well adapted to the data used. Nevertheless, the generalized gamma model is recommended because of the independence of the moment estimation errors with respect to the integration time step, which is not the case for the other models.